Chapter 16: Powders and Granules (A Text Book of Pharmaceutics for I Year Diploma in Pharmacy, 2024)
AuthorMr. Nadeem Hasan    Associate Professor, Dept. of Pharmaceutics, MAM College of Pharmacy, Kalaburagi, Karnataka, IndiaAbstract: Powders and granules are fundamental pharmaceutical forms used both as final dosage forms and as intermediates in the production of other solid dosage forms. This section explores the properties of powders, including particle size, shape, and surface area, and their impact on powder behavior and processing. Various methods of powder production, such as comminution and precipitation, are discussed. The principles of granulation, including wet and dry granulation techniques, are examined in detail, highlighting their role in improving powder flow properties and compressibility. Factors affecting granulation processes, such as binder selection, moisture content, and process parameters, are explored. The concept of particle size distribution and its measurement techniques are addressed. Quality control tests specific to powders and granules, including flow properties, bulk density, and moisture content determination, are detailed. Special considerations for effervescent granules and powder for reconstitution are discussed. The applications of powders and granules in various pharmaceutical dosage forms, including tablets, capsules, and sachets, are highlighted.Keywords: Particle characteristics, Flowability, Granulation, Size distribution, Compressibility, Process optimizationView PDF